Exploring the Positive Thinking of Patients With Prostate Cancer: Self-efficacy as a Mediator. Issue 2 (10th March 2022) - Chien, Ching-Hui; Chuang, Cheng-Keng; Liu, Kuan-Lin; Pang, See-Tong; Wu, Chun-Te; Chang, Ying-Hsu
Abstract : Background: Research has explored the effectiveness of positive thinking on individuals, but only a few studies have investigated the factors that influence individual positive thinking, particularly among patients with prostate cancer. Objectives: The aim of this study was to understand the factors that affect positive thinking among patients with prostate cancer and the mediating role of self-efficacy. Methods: A cross-sectional design and a convenience sampling method were used to recruit patients with prostate cancer from 2 hospitals in Taiwan. Structured scales were used for data collection, including the General Self-efficacy Scale, Expanded Prostate Cancer Index Composite, Positive Thinking Scale, and Social Support Scale. Results: The total average score for positive thinking among 201 patients was 66.1 (SD, 9.4). The factors that influenced the positive thinking of patients with prostate cancer included self-efficacy, treatment satisfaction, perceived health status, marital status, and appraisal support. The effects of treatment satisfaction and appraisal support on positive thinking were partly achieved through self-efficacy (partial mediation). Conclusions: Self-efficacy is a mediator that affects the relationship of treatment satisfaction, appraisal support, and positive thinking. Implications for Practice: In the course of the disease, healthcare providers can help patients with prostate cancer to promote and maintain appropriate positive thinking by improving treatment satisfaction; increasing appraisal support from family, relatives, and friends; strengthening self-efficacy; and modifying unrealistic expectations.